Potential Increase in Local Original Government Revenue (PAD) of Cilacap Regency from the Carbon Pricing Sector - Amru, Khaerul; Anjani, Raissa; Damanik, Mario; Wibisono, Suryo; Rahmila, Yulizar Ihrami (Department of Urban and Regional Planning, Diponegoro University, 2025)
Climate change in almost all regions including Indonesia not only has an impact on decreasing environmental quality, but also has an impact on the sustainability of the local economy. This is exacerbated by a decrease in carbon sequestration due to land use change and an increase in carbon emissions from various activities. This study aims to conduct an inventory of sequestration, emissions, and carbon valuation so that information about the potential increase in Regional Original Revenue (PAD) of Cilacap Regency from the carbon pricing sector can be obtained. Land cover data from Rupabumi Indonesia (RBI) was converted into carbon sequestration values according to the sequestration constant. Meanwhile, carbon emission data was obtained from Aksara-Bappenas. The results of the sequestration and emission are used for Net Zero Emission (NZE) evaluation which is then evaluated as a potential increase in PAD from the carbon pricing sector. This study showed the potential for sequestration and carbon emissions in the Cilacap Regency of 7,191,181.44 tons CO2 eq and 4.971.555,00 tons CO2 eq respectively. The sequestration that is greater than emissions shows the NZE achievement with an economic value of USD 4,439,252.88 or has the potential to increase PAD by 23.75% from 2022 gains.